2017
DOI: 10.1002/em.22138
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine‐induced mitotic catastrophe in Rad51d‐deficient mammalian cells

Abstract: Thiopurines are part of a clinical regimen used for the treatment of autoimmune disorders and childhood acute lymphoblastic leukemia. However, despite these successes, there are also unintended consequences such as therapyinduced cancer in long-term survivors. Therefore, a better understanding of cellular responses to thiopurines will lead to improved and personalized treatment strategies. RAD51D is an important component of homologous recombination (HR), and our previous work established that mammalian cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The induction of DNA damage is consistent with the known mechanism of action for thiopurines, further suggesting that the loss of NUDT15 exacerbates the DNA-directed effects of thiopurines. Of note, there was a striking difference in the level of 6-TG induced chromosomal aberrations, including dramatic increases in complex exchange events that were previously observed in HR-defective cells 23 . The work with cancer cells demonstrates that NUDT15-deficient cancer cells are sensitized to thiopurines and that the DNA-directed effects of thiopurines are exacerbated by NUDT15 deficiency.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…The induction of DNA damage is consistent with the known mechanism of action for thiopurines, further suggesting that the loss of NUDT15 exacerbates the DNA-directed effects of thiopurines. Of note, there was a striking difference in the level of 6-TG induced chromosomal aberrations, including dramatic increases in complex exchange events that were previously observed in HR-defective cells 23 . The work with cancer cells demonstrates that NUDT15-deficient cancer cells are sensitized to thiopurines and that the DNA-directed effects of thiopurines are exacerbated by NUDT15 deficiency.…”
Section: Discussionmentioning
confidence: 57%
“…This supports previous findings that cells progress though mitosis with doses of 6-TG, while higher doses of 6-TG cause a G 2 arrest. 23…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This protein-coding gene translates into a protein complex that promotes homologous pairing between single-and double-stranded DNA, homologous recombinant repair (HRR) pathways that can participate in the DNA replication process, and double-stranded DNA breaks occur during the overrun or are induced by DNA damage agents (Baldock et al 2019). Because RAD51D is an important part of homologous recombination, if this gene is defective, it will have a huge negative impact on cell mitosis; therefore, this gene plays an indispensable role in various biological processes of DNA (Wyatt et al 2018). Through transcriptome high-throughput sequencing and quantitative uorescence PCR experiments, we found that the expression level of RAD51D in the low-dose and high-dose groups was signi cantly higher than that in the blank group.…”
Section: Discussionmentioning
confidence: 99%